Development of a full ocean depth hydraulic manipulator with heavy-duty capacity - Ruan, Dongrui; Chen, Jiawang; Peng, Xiaoqing; Ai, Jingkun (Frontiers in Marine Science, 2024)
The underwater manipulator is a versatile tool commonly used for various underwater operations. In this study, we developed a heavy-duty hydraulic manipulator capable of operating at full ocean depth. The overall system design integrates both the mechanical structure and the electric control system. The master arm controls the slave arm by transmitting control signals to the controller and valve box. The structural design of the elbow and wrist joints has been optimized to enhance the manipulator's underwater performance and operational range. Laboratory tests demonstrated the manipulator’s excellent response consistency and tracking capability across a wide range of motion. During sea trials in the Mariana Trench, the manned submersible Fendouzhe successfully deployed the manipulator, showcasing its exceptional ability to complete complex tasks.